What causes mean reversion in corporate bond index spreads? The impact of survival - Bhanot, Karan (Journal of Banking & Finance, 2005)
Previous studies document that the spread between the yield on commonly used corporate bond indexes (e.g., Moody’s Baa index) and a comparable maturity treasury bond exhibits mean reversion. An analytical model shows that a part of the observed negative relationship between changes in the spread and the level of spreads is a natural consequence of ratings based classification of bonds included in the index and the related effects of survival. Using data on individual corporate bonds over the period January 1985 to December 1996, I corroborate the analysis and illustrate the effects of survival. The result has several implications for parametric specifications of spread dynamics in the pricing of contingent claims, for the application of spreads in tests of asset pricing models (such as the conditional version of the CAPM) and for the use of spreads in business cycle forecasts.